Study of polyphenolic compounds of Achillea Micranthoides Klok.et Krytzka Herbs - Dujun, I. F.; Mazulin, O. V.; Mazulin, G. V.; Дуюн, Ірина Федорівна; Мазулін, Георгій Владиленович; Мазулін, Олександр Владиленович (My University, 2017)
Achillea mickranthoides Klok. et Krytzka quantitative content of phenolic compounds in flowers and leaves by TLC and HPLC methoids.In herbal raw material identified 13 flavonoids and 10 hydroxycinnamic acids.In leaves and flowers the highest amount of neo-chlorogenic acid were determined.
Keywords: Achillea micranthoides Klok. et Krytzka; деревій подовий; flavonoids; флавоноїди; HPLC; ВЕРХ; hydroxycinnamic acids; гідроксикорични кислоти